Chinese Economic Engagement in Africa from the Perspective of International Law: The Practice of Anti-Neocolonialism - (:unkn) unknown (My University, 2022)
In recent years, with the convening of the Forum on China-Africa Cooperation in 2000 and the deepening of economic and trade relations between China and Africa, Chinese economic engagement in Africa has attracted greater attention from politicians, media and scholars in Western countries, and has been branded or characterized by "neo-colonialism" from time to time. It is impressive that the former U.S. secretary of state, Hillary Clinton had provoked discord in 2011 by warning Africans of Chinese "neo-colonialism." With the introduction and in-depth implementation of the “Belt and Road” Initiative, some Western media and politicians are more worried about China, trying to vilify and distort the "Belt and Road" initiative, rendering the assumption of the so-called "Chinese neo-colonialism" with color, and describing China-Africa economic cooperation as "neo-colonialism". For example, on December 30, 2014, CNBC criticized Chinese investment in Africa through raising colonialism questions. The English version of the New York Times put forward similar questions on May 1, 2017 when reporting Chinese investment in Africa, these were, "is China the world's new colonial power?" and "is China presenting a new model of development to the world”, or is the "Belt and Road" itself a new type of colonialism?" Even more alarming was the statement "China in Africa: neo-colonialism?" which was the subject of a hearing before a subcommittee of the United States Senate in 2018. Further, the New African Strategy of the United States used the phrase "predatory" practice while blaming China, but in essence, it is only another expression of "neo-colonialism". It is very visible that criticism from the western countries on Chinese "neo-colonialism" became regular after the "Belt and Road" initiative was proposed in 2013. Under the propaganda of Chinese "neo-colonialism", even exceptional officials from African countries echo this argument, and the writings of some schol
Keywords: African Research